Impact of enrichment medium on PCR-based detection of Listeria monocytogenes in food - Barbara JERŠEK; Tamara MAJSTOROVIĆ; Nataša KLUN; Sonja SMOLE MOŽINA (Acta Agriculturae Slovenica)
The detection of Listeria monocytogenes in food samples using enrichment and PCR is described. The objectives were to determine whether the type of enrichment medium has the influence on the results obtained with PCR and to evaluate proposed method by analysing naturally contaminated food samples. Comparative evaluation of different enrichment media for bacteria of the genus Listeria (half Fraser - HF, buffered peptone water - BPW, triptic soy yeast extract broth -  TSBYE, universal preenrichment broth - UPB) showed that only the UPB enabled detection of L. monocytogenes in artificially contaminated food samples after 24h of incubation. The PCR-based method gave equal results as standard cultural method by analysis of naturally contaminated food samples. Described PCR-based procedure is comparable to some other PCR-based methods of L. monocytogenes detection in foods and shows promise as a rapid, routine method which requires 30-72 h, whereas cultural methods require 96-120 h.